Prevalence of mental illness within families in a regional child‐focussed mental health service. (19th September 2017) - Naughton, Michael F. A.; Maybery, Darryl J.; Goodyear, Melinda
Abstract: Nearly 50% of all mental illnesses begin in childhood before the age of 14 years, and over 20% of parents have a mental illness. Few studies have examined the co‐occurrence of mental illnesses in parents and children. In the present study, we examined the extent of mental illness within families of 152 clients attending an Australian regional child and adolescent mental health service (CAMHS). A cross‐sectional study design was employed involving a case record review and clinician‐completed questionnaire of the children and youth attending a CAMHS. It was found that 79% of these children were living with a parent with mental illness. The predominant diagnosis of both child and parent was an anxiety or mood disorder, and many families had co‐occurring risk factors of domestic violence and limited social supports. The findings in this Australian cohort are similar to those of other international research. While novel in nature, the present study has highlighted the extent of both mental illness and scarce supports for both children and parents in the same family. The findings indicate the need for a coordinated multiservice delivery of appropriate and consistent family‐focussed interventions, responding to both mental illness and social supports for children and parents. Further research should examine specific components of family need and support, as seen through the eyes of the child and their parent.